Improving Working Conditions in Garment Supply Chains: The Role of Unions in Cambodia. (25th February 2015) - Oka, Chikako
Abstract: Given the disappointing outcomes of private regulation of labour in global supply chains, worker organization is increasingly seen as the key to better working conditions. This article examines the extent to which unions impact different dimensions of labour standard compliance in Cambodia's garment export sector, where unions have grown considerably. Based on unique factory‐level data and field‐based interviews, this study shows that union presence improves factories' compliance with wage, hours, and leave standards, although the impact is much less significant for health and safety. Moreover, having multiple unions in the workplace does not appear to improve labour conditions.